Large-scale friction control in turbulent wall flow - Schlatter, Philipp; Örlü, Ramis; Chin, Cheng; Hutchins, Nicholas; Monty, Jason (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
The present study reconsiders the control scheme proposed by Schoppa & Hussain [Phys Fluids 10:1049-1051 (1998)], using new sets of numerical simulations in a turbulent channel at a friction Reynolds number of 180. In particular, it is aimed at better characterising the physics of the control as well as investigate the optimal parameters. Results indicate that a clear maximum efficiency in drag reduction is reached for the case with a viscous-scaled spanwise wavelength of the vortices of 1200, which yields a drag reduction of 18%, contrary to the smaller wavelength of 400 suggested as the most efficient vortex in Schoppa & Hussain.
CRIS-Team Scopus Importer:2023-03-21